1999
DOI: 10.1111/j.1572-0241.1999.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Measurement of Lens Culinaris Agglutinin-Reactive Fraction of α-Fetoprotein As A Marker of Prognosis and Recurrence of Small Hepatocellular Carcinoma

Abstract: Measurement of AFP-L3% after treatment may be useful for understanding prognosis and recurrence of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 31 publications
3
38
0
Order By: Relevance
“…Finally, survival is longer in the patients with normal than in those with elevated AFP-L3% values. In summary, AFP-L3% is useful not only for diagnosis, treatment efficacy and recurrence of HCC, but also for assessing biological malignancy and the selection of therapeutic interventions [4,5,7].…”
Section: Afp-l3mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, survival is longer in the patients with normal than in those with elevated AFP-L3% values. In summary, AFP-L3% is useful not only for diagnosis, treatment efficacy and recurrence of HCC, but also for assessing biological malignancy and the selection of therapeutic interventions [4,5,7].…”
Section: Afp-l3mentioning
confidence: 99%
“…The difference is reflected on the binding activity to Lens culinaris agglutinin A. In practice, the percentage of AFP that binds with L. culinaris agglutinin A, referred to as APF-L3, is highly specific for the presence of HCC [1][2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…Another reported problem of AFP is low specificity because of a high false-positive rate with benign conditions such as acute and chronic active hepatitis (21)(22)(23)(24). Several authors have demonstrated that Lens culinaris agglutinin-reactive ·-fetoprotein (AFP-L3) can distinguish between HCC and hepatitis by detecting a sugar chain microheterogeneity (25)(26)(27). Our previous studies have demonstrated that glypican-3 (GPC3) is a novel tumor marker of HCC and is especially useful in the early stages because of its high sensitivity (28-31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HCC with high AFP-L3 levels demonstrate characteristics of advanced HCC by pathologic [13] and imaging findings [22]. Higher recurrence rates [23] and lower survival rates [12,14] after treatment have also been reported in patients with increased AFP-L3 at diagnosis. We sought to determine whether these benefits of AFP-L3 persist with hs-AFP-L3.…”
Section: Hs-afp-l3 For Evaluating the Prognosis Of Patients With Hccmentioning
confidence: 95%